PIXSIC: A Wireless Intracerebral Radiosensitive Probe in Freely Moving Rats. Issue 9 (1st September 2015) - Balasse, Laure; Maerk, Julia; Pain, Frédéric; Genoux, Aurelie; Fieux, Sylvain; Lefebvre, Françoise; Morel, Christian; Gisquet-Verrier, Pascale; Lanièce, Philippe; Zimmer, Luc
The aim of this study was to demonstrate the potential of a wireless pixelated β+-sensitive intracerebral probe (PIXSIC) for in vivo positron emission tomographic (PET) radiopharmacology in awake and freely moving rodents. The binding of [ 11 C]raclopride to D2 dopamine receptors was measured in anesthetized and awake rats following injection of the radiotracer. Competitive binding was assessed with a cold raclopride injection 20 minutes later. The device can accurately monitor binding of PET ligands in freely moving rodents with a high spatiotemporal resolution. Reproducible time-activity curves were obtained for pixels throughout the striatum and cerebellum. A significantly lower [ 11 C]raclopride tracer-specific binding was observed in awake animals. These first results pave the way for PET tracer pharmacokinetics measurements in freely moving rodents.